(untitled) (Fiep Bulletin - online, 2015)
Leisure is important for all individuals, but for children is a fundamental activity for development, social integration and creation of a horizontal attachment, or attachment with children of the same age, which will be able to grasp concepts like cooperation, competition and privacy. The aim of this study was to identify the practices of children’s leisure Apodi to examine whether leisure is influencing children in their development. Descriptive - for such analysis, a field survey was conducted quantitative trait. A questionnaire with 10 multiple choice questions, 96 students participated in the survey aged 6, 7 and 8 years studying 1st and 2nd year of elementary school I was applied, the results showed that children’s leisure practices though are made below what is needed for the development of children.